2019
DOI: 10.7150/jbji.30636
|View full text |Cite
|
Sign up to set email alerts
|

Association between Allogeneic Blood Transfusion and Wound Infection after Total Hip or Knee Arthroplasty: A Retrospective Case-Control Study

Abstract: Abstract. Background: To assess using a retrospective case control study, whether patients undergoing primary, elective total hip or knee arthroplasty who receive blood transfusion have a higher rate of post-operative infection compared to those who do not.Materials and Methods: Data on elective primary total hip or knee arthroplasty patients, including patient characteristics, co-morbidities, type and duration of surgery, blood transfusion, deep and superficial infection was extracted from the Alberta Bone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
0
25
0
2
Order By: Relevance
“…Allogeneic blood transfusion is associated with an increased risk of surgical site infection and PJI. [ 6 - 8 ] This has been hypothesized to be related to the immunomodulatory effects of transfusion. The results of our study confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic blood transfusion is associated with an increased risk of surgical site infection and PJI. [ 6 - 8 ] This has been hypothesized to be related to the immunomodulatory effects of transfusion. The results of our study confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid (TA) is a synthetic antifibrinolytic substance that inhibits proteolytic degradation of fibrin by blocking the lysine binding sites of allogenic blood transfusion causes alteration in immune system which can result in higher risk of surgical site infection. [6][7][8] Thus TA may reduce the rate of early and delayed PJI. In this study, we aimed to analyze the effect of intravenous administration of TA on reducing the risk of revision for acute and delayed PJI after primary TKR.…”
mentioning
confidence: 99%
“…Our study also found higher rates of transfusion rates in the DDH cohort. This is concerning as higher allogeneic blood transfusion after arthroplasty have been associated with higher odds of mortality and increased superficial and deep wound infections [23,24].…”
Section: Discussionmentioning
confidence: 99%
“… 66 A more recent retrospective case control study involving more than 27,000 patients undergoing primary THA and TKA demonstrated an overall incidence of blood transfusion of 11.1%, which was associated with a significantly increased risk of superficial infection (adjusted odds ratio [ OR ] 1.9 [95% CI 1.2–2.9, p-value 0.005]) as well as deep infection (adjusted OR 1.6 [95% CI 1.1–2.2, p-value 0.008]). 67 A study involving 2760 patients undergoing primary hip and knee arthroplasty procedures in Germany, showed that the overall complication rate in patients who received transfusions was 34.7% compared with 13.2% in patients who did not require transfusion, with infection rates of 2.82% and 0.4% respectively. 68 …”
Section: Blood Transfusionmentioning
confidence: 99%